Holder’s Inequality for the Polar Derivative of Polynomial Having All Zeros inside a Disk - Lal, R. (Journal of Scientific Research, 2020)
In this paper, we have proved an Lp inequality for polar derivative of the polynomial having all its zeros in the disk |Z|≤ k, k ≤ 1. Our result generalizes and improves the earlier known results.